Extracellular vesicles therapy alleviates cisplatin-ınduced testicular tissue toxicity in a rat model - Halime Tozak Yıldız; Kübra Tuğçe Kalkan; Numan Baydilli; Zeynep Burçin Gönen; Özge Cengiz Mat; Eda Köseoğlu; Gözde Özge Önder; Arzu Yay (PLoS ONE, 2025)
Purpose Cisplatin is a commonly used chemotherapy agent effective against various cancers, however it induces significant gonadotoxicity and infertility due to its adverse effects on testicular function. The underlying mechanisms of cisplatin-induced testicular damage include oxidative stress and dysregulated autophagy. This study investigates the potential of extracellular vesicles (EVs) to mitigate cisplatin-induced testicular damage through their regenerative, antioxidant, and autophagy-modulating properties. Methods In the testicular toxicity model, thirty-two male rats were randomly divided into four groups (n = 8): control, EVs-only, Cis-only, and Cis + EVs. A single intraperitoneal dose of 7.5mg/kg cisplatin was administered on the first day. On the six day, the EVs treatment group received a single dose of EVs (8x107/100μl) intravenously. Animals were sacrificed on day eight. Testicular histoarchitecture was assessed via hematoxylin and eosin staining. Sperm parameters, including motility and count, were measured using light microscopy. Hormone levels (testosterone and inhibin) were determined via enzyme-linked immunosorbent assay (ELISA). Oxidative stress markers, such as glutathione peroxidase (GSH-PX), superoxide dismutase (SOD), catalase (CAT), and is a metabolite malondialdehyde (MDA), were quantified using colorimetric assays. Autophagy and steroidogenesis were evaluated through immunohistochemical analysis of Beclin-1, p62, LC3–2, SF-1, and StAR. Results Cisplatin exposure caused significant testicular damage, characterized by reduced germinal epithelium and degeneration of seminiferous tubules (p < 0.001). These structural changes led to hormonal imbalances, as evidenced by declines in testosterone (p < 0.005) and inhibin (p < 0.001). Additionally, sperm motility (p < 0.05) and count (p < 0.001) were adversely affected. Immunohistochemical analysis revealed upregulation of autophagy markers (p < 0.001), indicating heightened autophagic activity, alongside downregulation of steroidogenic factors (p < 0.001), which contributed to impaired steroidogenesis. Elevated levels of malondialdehyde (MDA) (p < 0.01) and decreased activities of antioxidant enzymes—GSH-PX, SOD, and CAT (p < 0.001) pointed to increased oxidative stress as a contributing mechanism. In contrast, treatment with extracellular vesicles (EVs) significantly improved testicular histoarchitecture (p < 0.001) and restored hormonal levels toward normal (testosterone p < 0.005, inhibin p < 0.001). Furthermore, EVs reduced the expression of autophagy markers (p < 0.001) and enhanced the levels of steroidogenic factors (p < 0.05). Notably, MDA levels decreased (p < 0.001), while antioxidant activities increased (p < 0.001), suggesting a protective effect of EVs against oxidative stress. Conclusion EVs protect against cisplatin-induced reproductive toxicity by modulating oxidative stress and autophagy pathways, preserving testicular function and fertility. These findings suggest that EVs may be a promising therapeutic strategy for mitigating cisplatin’s negative effects on reproductive health. Further exploration of dosing regimens and localized applications is recommended for improved efficacy.